PERIPHERAL OSTEOMA OF THE MANDIBLE: A CASE REPORT* - Mustafa GÜMÜŞOK; Şerife DEĞERLİ; Mehmet Emin TOPRAK; Anıl SEÇKİN2; Elif KAYA; Burcu ŞENGÜVEN (Istanbul University, 2015)
Osteomas are benign tumors which are composed of mature compact or cancellous bone. They can be either peripheral, central or extraskeletal. The peripheral osteoma arises from surface of the bone (periosteal) whereas the central osteoma arises from the bone medullary (endosteal) and the extra-skeletal soft tissue osteoma usually develops within the muscle. Osteomas are most commonly found in the skull and facial bones. Multiple osteomas may be associated with Gardner's Syndrome. These lesions are usually painless and recurrence is uncommon after local excision. In this case report clinical, radiographic findings and treatment of a 24-year-old male patient with peripheral osteoma in the anterior mandible are presented.